EVALUASI DAN STRATEGI PENGELOLAAN PENYADAPAN POHON PINUS SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DI SUMEDANG, JAWA BARAT - Desiana - Zulvianita; Rina Ratnasih Purnamahati; Angga Dwiartama (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
The increase in economic needs has resulted in increased community pressure on forest area. This encourage the government to open up access to utilize forest, in order to improve the community's economy. Since March 2018, access to utilize forest has been implemented in Masigit Kareumbi Game Reserve (TBMK). However, research related to the evaluation of activities has not been widely found. This study aims to evaluate and determine the optimal pine tapping management strategy in TBMK. The research was conducted in Sukajaya and Citengah Villages, South Sumedang District, using Ostrom Institutional Analysis and Development Framework, Stakeholder Analysis, and the Analysis Hierarchy Process. The result showed that, the potential of pine resin in the research location was 308,377.3 kg/year, which had a positive economic, social, and institutional impact on the community but tended to have a negative impact on the ecological aspects. Stakeholder analysis showed that the parties involved were among others KLHK, BBKSDA West Java, Sukajaya and Citengah Heads Village, Forest Farmer Group (KTH) Sawargi and Medal Kencana, Pinus Merkusii Cooperation, and the Indonesian Conservation Cadre Communication Forum (FK3I). Each stakeholder has a good relationship, however, there is still a need for a more optimal communication and coordination system between one another. The suggested strategy is to increase community assistance by FK3I and Pinus Merkusii Cooperation involvement in limiting the tapping pine resin.